Principle of Sovereign Equality and Non-Interference in the Internal Affairs of A State - jean Luc, Kizito Cimanuka (Tirtayasa Journal of International Law, 2022)
The principle of non-interference is one of the fundamental principles of international relations. It thus has a fundamental aspect.  But questions were raised about the legitimacy of humanitarian interference as an exception to the principle. Chapter VII of the San Francisco Charter already provides for an exception of interference in the event of a breach of international peace and security. That said, reflection will be made on the very principle of non-interference, which calls on other principles that are its presuppositions. Only then will a theoretical examination be made of the exceptions limiting the very scope of the principle of non-interference. We will be comfortable in affirming the existence of the principle of non-interference only if and only if certain principles have been acquired, such as the prohibition of the use of force, the self- determination of peoples, respect for territorial integrity, to name but a few. However, it will be inconvenient for us to discuss the presuppositions of the principle of non-interference before identifying the scope and scope of the concept and its basis.